SYNTHESIS OF SOLID COMPOUNDS OF Fe_2O_3–Nb_2 AND INVESTIGATION OF THEIR ELECTROPHYSICAL AND PHOTOELECTROCHEMICAL PROPERTIES - Arakelyan, V. M.; Galstyan, V. E. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
The efficiency of the solar energy conversion by water photoelectrolysis method is mainly determined by the properties of the semiconductors photoanode which performs function of photocataliser. One of the perspective ways of optimization of these parameters is the usage of the new triple- and four-compound metal-oxide. For this purpose solid solutions of different compounds in Fe2O3– Nb2O5 system are synthesized. The electrophysical and electrochemical properties of the synthesized samples are studied. It is shown that the electrodes made on the base of homogeneous solid solution of FeNbO4 provide efficient photoelectrolysis process at the most optimal combination of important parameters.